2010
DOI: 10.1108/00242531011065091
|View full text |Cite
|
Sign up to set email alerts
|

Librarians and controlling disinformation: is multi‐literacy instruction the answer?

Abstract: Purpose -Librarians have long been part of a group of professionals that took responsibility for the reliability of information and protected their users from the bad epistemic consequences caused by inaccurate information. Now users are acquiring information from the internet and using it to make important decisions. This method of acquisition is threatening the epistemological protection librarians have provided. The problem is one of verifiability, the users do not have a way to verify whether information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…Conroy et al (2015) identified three broad types of fake information, namely, serious fabrications, large-scale hoaxes and humorous fakes, each having a different intention from the other. In this context, the term misinformation refers to information that is not true or inaccurate, which may sometimes be RSR 46,1 produced as honest mistakes (Walsh, 2010). Honest mistakes may include false information being shared by real journalists or credible mainstream media outlets, which give them the sense of authenticity (Schifferes et al, 2014) that eventually mislead people.…”
Section: Fake News Judgementmentioning
confidence: 99%
“…Conroy et al (2015) identified three broad types of fake information, namely, serious fabrications, large-scale hoaxes and humorous fakes, each having a different intention from the other. In this context, the term misinformation refers to information that is not true or inaccurate, which may sometimes be RSR 46,1 produced as honest mistakes (Walsh, 2010). Honest mistakes may include false information being shared by real journalists or credible mainstream media outlets, which give them the sense of authenticity (Schifferes et al, 2014) that eventually mislead people.…”
Section: Fake News Judgementmentioning
confidence: 99%
“…These include reexamining the scope and focus of IL (e.g., critical IL, IL 2.0, and meta-literacy), developing standards and best practices, and conducting empirical investigations on students' social media information behavior. In terms of the last category, most studies have focused on perception and use of social media (e.g., Kim, Sin, & Tsai, 2014;Lim, 2009;Morris, Teevan, & Panovich, 2010;Zhang, 2012), as well as on the criteria and strategies used in evaluating the credibility of social media information (e.g., Kim & Oh, 2009;Lim, 2013;Walsh, 2010). Extant studies are invaluable in shedding light on students as consumers of social media information.…”
Section: Introductionmentioning
confidence: 98%
“…It may result from many objective factors, and in the opinion of information holder may be intentionally accurate. At the other hand, disinformation includes element of intention, is inaccurate as a result of desire of purposeful confusion of another user (Walsh 2010). In the literature of subject one may encounter approaches differentiating semantic content value, which were accidentally damaged and become false information from those, which are to be damaged on purpose-disinformation (Fallis 2011).…”
Section: )mentioning
confidence: 99%